Mixed methods research on satisfaction with basic medical insurance for urban and rural residents in China - Xiaofang Liu; Fang Yang; Wenwei Cheng; Yanyan Wu; Jin Cheng; Weichu Sun; Xiaofang Yan; Mingming Luo; Xiankun Mo; Mi Hu; Qian Lin; Jingcheng Shi (BMC, 2020)
Abstract Background There have been few studies on satisfaction with integrated basic medical insurance for urban and rural residents (URRBMI), and satisfaction with URRBMI is not very high because of the complexity of its policies and differences among the insured. The aim of the present study was to explore the factors that influence satisfaction with URRBMI in China and to provide scientific suggestions to the government for how to effectively manage and improve the policy. Methods An explanatory sequential design of mixed methods research was used. A quantitative research using a three-stage stratified cluster sampling method was used to randomly select the guardians of pupils who participated in URRBMI (n = 1335). The quantitative research was conducted to calculate the latent variables' scores and path coefficients between latent variables using SmartPLS3.0. With public trust, public satisfaction, and perceived quality as the target variables, important-performance analysis (IPA) was used to explore the important but underperforming factors, which were the key elements to improving satisfaction with URRBMI. A purposeful sampling strategy according to satisfaction level was used to obtain qualitative research subjects from among the quantitative research subjects. A qualitative research was conducted using semi-structured interviews, and the thematic analysis method was used to summarize the interview data. Results The three strongest paths were perceived quality to public satisfaction, with a total effect of 0.737 (t = 41.270, P < 0.001); perceived quality to perceived value, with a total effect of 0.676 (t = 31.964, P < 0.001); and public satisfaction to public trust, with a total effect of 0.634 (t = 31.305, P < 0.001). IPA revealed that public satisfaction and perceived quality were key factors for public trust and that perceived quality was of high importance for public satisfaction but had low performance. The policy quality was a determining factor for perceived quality. The qualitative research results showed that the most unsatisfactory aspect for the insured was the policy quality. Conclusions This study found that improving quality is key to improving public satisfaction with and public trust in URRBMI. The government should improve the compensation level by broadening the channel of financing for the URRBMI fund, rationally formulating reimbursement standards, and broadening the scope of the drug catalog and the medical treatment projects. The government should establish a stable financing growth mechanism and effective methods of providing health education to improve public satisfaction and public trust.